Quantum Optics: A Scientometric Assessment of India’s Publications during 1996-2021 - Gupta, BM; Kappi, Mallikarjun; Walke, Rajpal; Biradar, BS (Journal of Data Science, Informetrics, and Citation Studies)
Objectives: The present study examines the publication output of authors from India on the topic of “Quantum Optics” during 1996-2021 using bibliometric methods. Methods: The Indian publications as listed in the Scopus database were identified by using “Quantum Optics” in the “Title” tag. Results: 67274 global publications emerged on the topic of “Quantum Optics” during 1996-2021. India contributed only 2108 publications on this topic and constituted a 3.13% share of global output. About 30.0% share of Indian publications received external funding support and were involved in international collaboration, respectively. The 455 organizations and 635 authors participated unevenly in the research on this topic, with the highest number of publications (96) emerging from the Indian Institute of Science, Bangalore, followed by the University of Calcutta (80 publications), Harish Chandra Research Institute, Allahabad (69 publications) and Tata Institute of Fundamental Research, Mumbai (68 publications). Indian Association for Cultivation of Science (IACS), Kolkata (69.9 and 5.68) registered the highest citation impact per paper and relative citation index, followed by Physical Research Laboratory, Ahmedabad (23.23 and 1.89), Harish Chandra Research Institute, Allahabad (22.93 and 1.86) and Tata Institute of Fundamental Research, Bombay (22.72 and 1.85). The highest number of publications (33) is contributed by G.S. Agarwal, followed by A.K. Pati (32 papers), A. Pathak (31 papers), and P.K. Panigrahi (29 papers). G.S. Agarwal (40.82 and 3.32) registered the highest citation impact per paper and relative citation index, followed by P.K. Panigrahi (21.83 and 1.77), A.K. Pati (21.06 and 1.71), and A. Pathak (19.87 and 1.61). The journals that published the highest number of publications (233) were Physical Review A (233 papers), Quantum Information Processing (109 papers), Physics Letters Section A (74 papers), and Spectrochimica Acta Part A (61 papers). Physical Review Letters (62.30) was the most impactful journal in terms of citations per paper, followed by the Journal of Optics (United Kingdom) (24.92), Physical Review E (19.07), and Journal of Optics B. Quantum & Semiclassical Optics (18.85), Journal of Physical Chemistry C (18.58). The most commonly investigated topics (keywords) in terms of frequency of appearances were quantum optics (1390), followed by nonlinear optics (520), quantum theory (407), quantum entanglement (283)), photons (223), and quantum computers (223). Conclusion: Over the last two decades a large number of publications have emerged in the area of “Quantum Optics”, which are creating a significant impact on the development of many diverse quantum technologies both in India and abroad.
Keywords: Quantum Optics; India; Publications; Bibliometrics; Scientometrics.